ANALISIS PENGARUH PENDAPATAN, HARGA, DAN JUMLAH ANGGOTA KELUARGA TERHADAP PERMINTAAN IKAN LAUT SEGAR DI KELURAHAN KUALA SAMBOJA KECAMATAN SAMBOJA - Andi Fira Ramadhani; Helminuddin; Nurul Ovia Oktawati (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
This research is aimed to Analyze The Impact Of Income, Price, And Number Of Family Members On Demand For Sea Fish In Kuala Samboja Village In District Samboja both simultaneously and partially and to know the independent variable which was the most dominant among income, price, and number of family members. The research was conducted in Kuala Samboja Village In District Samboja. The sample of this research are misters and mistresses who live in Kuala Samboja Village. The number of samples are 30 people which then the researcher use Systematic Random Sampling. The result of this research shows that on simultan way independent variables (X1, X2, X3) have a significant impact on dependent variable (Y), while on partial way variable of fish's price (X2) has a significant impact on dependent variable (Y). The most dominant variable among 3 (three) independent variables (X1, X2, X3) is fish's price factor which is shown by the value of ß standardized coefficients that has the greatest value. Keywords: Income, Price, Number of Family Members, Demand, Kuala Samboja Village.